2011
DOI: 10.1002/adfm.201100041
|View full text |Cite
|
Sign up to set email alerts
|

Localized Ligand Induced Electroless Plating (LIEP) Process for the Fabrication of Copper Patterns Onto Flexible Polymer Substrates

Abstract: The “ligand induced electroless plating (LIEP) process” is a simple process to obtain localized metal plating onto flexible polymers such as poly(ethylene terephtalate) and polyvinylidene fluoride sheets. This generic and cost‐effective process, efficient on any common polymer surface, is based on the covalent grafting by the GraftFast process of a thin chelating polymer film, such as poly(acrylic acid), which can complex copper ions. The entrapped copper ions are then chemically reduced in situ and the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
83
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 48 publications
3
83
0
Order By: Relevance
“…Metallic thin films on desired surfaces with strong adhesion can be obtained as clearly demonstrated in previous publications. [12][13][14] More importantly, success in modification of titanium nitride with amino groups would extend the application of this ceramic material towards biosensor development. 15 Hence it is worth underlying the importance of development of efficient organic coating techniques for covalent functionalization of titanium nitride surface.…”
Section: Introductionmentioning
confidence: 99%
“…Metallic thin films on desired surfaces with strong adhesion can be obtained as clearly demonstrated in previous publications. [12][13][14] More importantly, success in modification of titanium nitride with amino groups would extend the application of this ceramic material towards biosensor development. 15 Hence it is worth underlying the importance of development of efficient organic coating techniques for covalent functionalization of titanium nitride surface.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, iron powder is added as a chemical reducer to generate the aryl radical [39]. This wet chemical treatment called Graftfast process is employed to modify polyvinylidene fluoride membranes, poly(ethylene terephthalate), acrylonitrile-butadiene-styrene polymers and polyvinylchloride (PVC) polymers [39][40][41][42]. Chehimi et al also observed that the aryl radical generated from aryldiazonium salt could be covalently grafted onto a polymeric surface such as poly(methyl)methacrylate [43].…”
Section: Introductionmentioning
confidence: 96%
“…Sintering free, high conductivity and the usage of non-noble metal as conductive material are the strengths of this process. But the poor adhesion of the patterns is the major problem for the lack of interaction between catalyst and polymer substrate [23][24][25][26][27]. Self-assembly of polyelectrolyte, surface grafting of polymer, surface modification of coupling agent, etc.…”
Section: Introductionmentioning
confidence: 99%